2001
DOI: 10.1086/317644
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis Progression Is Related to CD4 Cell Depletion in Patients Coinfected with Hepatitis C Virus and Human Immunodeficiency Virus

Abstract: A total of 204 patients with liver biopsy-proven hepatitis C virus (HCV) infection, 84 with and 120 without human immunodeficiency virus (HIV) coinfection, were studied, to evaluate variables possibly associated with the stage of liver fibrosis. All patients were injection drugs users, with a mean age of 32 years and an estimated duration of HCV infection of 12 years. Twenty-four patients (11%) had many fibrous septa with (5%) or without (6%) cirrhosis, 56 (27%) had few fibrous septa, and 124 (60%) had no fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(128 citation statements)
references
References 13 publications
8
117
2
1
Order By: Relevance
“…The more rapid progression of hepatic disease with co-infection is currently unexplained. It has also been shown that co-infected patients have a higher incidence of fibrosis (6,7). Furthermore, a greater degree of portal, periportal, and lobular inflammation (centrilobular fibrosis, cholestasis, and granulocytic cholangiolitis) was reported in patients with HCV/HIV co-infection than with HCV alone (8).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…The more rapid progression of hepatic disease with co-infection is currently unexplained. It has also been shown that co-infected patients have a higher incidence of fibrosis (6,7). Furthermore, a greater degree of portal, periportal, and lobular inflammation (centrilobular fibrosis, cholestasis, and granulocytic cholangiolitis) was reported in patients with HCV/HIV co-infection than with HCV alone (8).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…CD4 cell count , 200 mm 3 ) has been independently associated with an increased risk of advanced histologic and/or clinical liver disease in persons coinfected with HIV and hepatitis C [6,9,19,20]. This inverse relationship of CD4 cell count and liver disease supports the hypothesis that reversal or prevention of immunosuppression with HAART will decrease the rate of HCV fibrosis progression and the risk of cirrhosis and its clinical consequences (ESLD, hepatocellular carcinoma and death) in HIV-infected patients.…”
mentioning
confidence: 66%
“…HCV is not directly cytopathic and the pathogenesis of liver injury is believed to be immune mediated [21]. It can be argued that HIV patients should develop less severe liver injury because of the immune suppression [22].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals infected with HCV genotype 2, 3 have better response than HCV genotypes 1, 4 "like the situation in Egypt, where genotype 4 is predominant" [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Also the number of HIV patients included in our study was too small to draw definitive conclusions.…”
Section: Hiv Prevalence Among Hcv Egyptian Infected Patients and Its mentioning
confidence: 99%